2014
DOI: 10.1038/bjc.2014.490
|View full text |Cite
|
Sign up to set email alerts
|

Serpin peptidase inhibitor clade A member 1 is a biomarker of poor prognosis in gastric cancer

Abstract: Background:In a previous study, we reported that serpin peptidase inhibitor clade A member 1 (serpinA1) is upregulated in Snail-overexpressing gastric cancer. Although serpinA1 has been studied in several types of cancer, little is known about its roles and mechanisms of action. In this study, we examined the role of serpinA1 in the migration and invasion of gastric cancers and determined its underlying mechanism.Methods:Expression levels were assessed by western blot analyses and real-time PCR. Snail binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…Increased levels of SERPINA1 have been observed in plasma [14] as well as gastric juice [38] of gastric cancer patients. SERPINA1 has been shown to induce invasion and migration of gastric cancer cells and has been associated with poor prognosis [39]. ITIH3 is a member of the inter-alpha-trypsin inhibitor family of plasma serine protease inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Increased levels of SERPINA1 have been observed in plasma [14] as well as gastric juice [38] of gastric cancer patients. SERPINA1 has been shown to induce invasion and migration of gastric cancer cells and has been associated with poor prognosis [39]. ITIH3 is a member of the inter-alpha-trypsin inhibitor family of plasma serine protease inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…(plasminogen activator inhibitor-1) were proposed as targets for diagnosis but also therapy in cancer (32)(33)(34). (38,39) but also in several diseases (36).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to exhibit an invasive and metastatic capacity in lung cancer, gastric cancer, and colorectal cancer (43,44). Previous studies have revealed that SerpinA1 may serve as a biomarker for gastric cancer as it induces the invasion and migration of gastric cancer cells, and its expression is associated with the progression of gastric cancer (45). ORM2 is an important acute phase plasma protein due to its increased abundance during acute inflammation.…”
Section: Discussionmentioning
confidence: 99%